2018
DOI: 10.1097/mpa.0000000000001063
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Chemotherapy for Advanced Rare Pancreatic Histotype Tumors

Abstract: Because of the lack of clinical trials in patients affected by these rare pancreatic histotypes, only their molecular classification would help clinicians in future therapeutic choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 91 publications
3
27
1
Order By: Relevance
“…10,11,18) around the body and tail of the pancreas were dissected)this concurs with the previous findings of Suzuki et al 22 The role of neo-adjuvant or adjuvant chemotherapy, and radiotherapy, in the treatment of SPT is limited, 23,24 but Brunetti et al find an interesting result that a patient diagnosed to SPTP with malignant transformation treated with adjuvant chemotherapy achieved a longduration. 25 In the present study, we found that pancreatic fistulas were the predominant complication (n=21 patients); grade A fistulas were found in 19 patients, while grade B fistulas were found in two patients; we did not identify any grade C fistulas. Postoperative bleeding was the most dangerous complication and one of the patients who underwent vascular resections suffered hemorrhage post operation and was cured by conservative treatment such as drainage and hemostatic.…”
Section: Discussioncontrasting
confidence: 45%
“…10,11,18) around the body and tail of the pancreas were dissected)this concurs with the previous findings of Suzuki et al 22 The role of neo-adjuvant or adjuvant chemotherapy, and radiotherapy, in the treatment of SPT is limited, 23,24 but Brunetti et al find an interesting result that a patient diagnosed to SPTP with malignant transformation treated with adjuvant chemotherapy achieved a longduration. 25 In the present study, we found that pancreatic fistulas were the predominant complication (n=21 patients); grade A fistulas were found in 19 patients, while grade B fistulas were found in two patients; we did not identify any grade C fistulas. Postoperative bleeding was the most dangerous complication and one of the patients who underwent vascular resections suffered hemorrhage post operation and was cured by conservative treatment such as drainage and hemostatic.…”
Section: Discussioncontrasting
confidence: 45%
“…Acinar cell carcinoma (ACC) is an extremely rare pancreatic tumor comprising 1%‐2% of pancreatic tumors with 50% of tumors presenting with metastases at the time of diagnosis and those patients with advanced disease (Stage III and IV) having very poor prognosis . Cross‐sectional imaging modalities such as computed tomography and magnetic resonance imaging that are enhanced with contrast agents are often utilized to define the extent of primary lesions and possible metastatic disease .…”
Section: Discussionmentioning
confidence: 99%
“…Small cohort studies and case reports list a number of regimens with an overall response rate of 23% and a median PFS of 5.6 mo (Al-Hader et al 2017;Yoo et al 2017). Chemotherapeutic substances include gemcitabine, capecitabine, 5-fluoruracil, irinotecan, cisplatin/oxaliplatin, and taxanes (Lowery et al 2011;Al-Hader et al 2017;Yoo et al 2017;Brunetti et al 2018) and also targeted therapies such as erlotinib or panitumumab in KRAS wild-type tumors (Morales et al 2013;Kruger et al 2016). Regarding predictors of treatment response, defects in DNA repair genes such as BRCA1, BRCA2, and PALB2 have been linked to prolonged survival following platinum-based regimens in some patients (Al-Hader et al 2017;Yoo et al 2017).…”
Section: Discussionmentioning
confidence: 99%